1992
DOI: 10.1002/qua.560420524
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of the role of hydration in nucleic acid structure and function

Abstract: The results of the Monte Carlo Metropolis simulation of water structure and of the hydration of nucleic acid fragments, complementary base pairs and mispairs, base pair stacks, and duplex fragments have been summarized. Systematic investigations suggest some general conclusions: (1) the hydration shell structure of the major and minor grooves of the duplex depends significantly on DNA conformation (or stack configuration) and nucleotide sequence, while global hydration characteristics (average energy, the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…In order to investigate an ability of the N(3) atom to formation of such hydrogen bonds we consider complex of guanine with 17 water molecules. Starting geometry of this complex has been Table 4 Geometry and values of the electron density (q) and the Laplacian of the electron density (r 2 q) in the (3,-1) bond critical point of the hydrogen bonds in the guanine Á 16H 2 built by addition of one water molecule to optimized structure of G16W complex above the N(3) atom.…”
Section: Modeling Of O-háááp Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate an ability of the N(3) atom to formation of such hydrogen bonds we consider complex of guanine with 17 water molecules. Starting geometry of this complex has been Table 4 Geometry and values of the electron density (q) and the Laplacian of the electron density (r 2 q) in the (3,-1) bond critical point of the hydrogen bonds in the guanine Á 16H 2 built by addition of one water molecule to optimized structure of G16W complex above the N(3) atom.…”
Section: Modeling Of O-háááp Interactionsmentioning
confidence: 99%
“…The water plays a central role in the maintenance of the three-dimensional architecture of nucleic acids [1][2][3]. Most, if not all, of the properties of nucleic acids are related to the presence of a hydration shell surrounding each nucleotide [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance small number of different coordination numbers and coordination polyhedra were found in hydration shell of cations [36]. Analyses of F-structures of the system DNA fragment-water showed that carbonyl oxygen atoms of nucleic acid bases are always hydrated by two water molecules [37], though according to the study of I-structure ensembles hydration numbers of these atoms are fractional and less then two.…”
Section: Instantaneous and Inherent Structuresmentioning
confidence: 99%
“…Although it is well established now that the DNA polymorphism can be induced by changes in the solvating conditions, the mechanism of these transitions on the molecular level is not fully clarified. The concept of"hydration economy'' proposed by Saenger( 5) to explain B to A DNA transition has been recently supported by Monte Carlo Metropolis simulations (6,7). In contrast, the RNA structure seems to be quite insensitive to variations in the degree of hydration (8).…”
Section: Introductionmentioning
confidence: 96%